Peranan Komunikasi Organisasi dalam Manajemen Konflik - Fauzan Ahmad Siregar; Lailatul Usriyah (Idarah (Jurnal Pendidikan dan Kependidikan), 2021)
Contemporary view showed the position of communication to achieve educational organization purpose. Besides, communication has important role to create organization individual attitude. The importance of organization in education organization to minimize bad conflict. The result of this study showed that communication has taken preventive and represive steps to manage conflict in the organization. Communication also has important role to implemented conflict management activities in the organization. Communication also has informative, regulative, persiasive and integrative roles to manage conflict in organization.